Enantioselective Potentiometric Membrane Electrodes Based on Antibiotics for the Determination of L- and D-Glyceric Acids - Raluca-Ioana Stefan-van Staden; R'afat M. Nejem; Jacobus Frederick van Staden; Hassan Y. Aboul-Enein (International Journal of Electrochemistry)
Glyceric acid (GA) is a human metabolite existing in L- and D-configurations, which are considered the markers for the diseases L- and D-glyceric aciduria/academia, respectively. Enantioselective, potentiometric membrane electrodes based on carbon paste modified with antibiotics as chiral selectors, vancomycin, and teicoplanin were designed for the assay of L- and D-GA, respectively, in the concentration ranges of 10−9–10−7 and 10−4–10−2 moL/L with very low detection limits (1.5 × 10−10 moL/L for L-GA and 1.6 × 10−4  moL/L for D-GA, resp.). The surface of the electrodes can be regenerated simply by polishing in order to obtain a fresh surface ready to be used in a new assay. The proposed electrodes can be successfully applied for the enantioanalysis of L- and D-glyceric acids in serum samples.